1998
DOI: 10.1007/s002130050710
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary inositol enhances locomotor activity and brain inositol levels in rats

Abstract: myo-Inositol has been found to be clinically effective in depression, obsessive compulsive disorder (OCD) and panic disorder when given chronically per os. The present study examined the effects of chronic dietary inositol in rats on locomotor behaviour. Regional brain levels of inositol were analyzed by gas chromatography. Chronic dietary inositol significantly enhanced locomotion and rearing in rats and elevated inositol levels by 36% in the cortex and 27% in hippocampus. No differences in inositol levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
9
2
Order By: Relevance
“…In contrast to the literature reports mentioned above (13,14), our study showed that the greatest increase in myo-Ins (23%) occurred in the cerebellum (Fig. 2), followed by the brainstem and hippocampus (18% and 17%, respectively).…”
Section: Effects On Myo-ins Concentrationscontrasting
confidence: 85%
“…In contrast to the literature reports mentioned above (13,14), our study showed that the greatest increase in myo-Ins (23%) occurred in the cerebellum (Fig. 2), followed by the brainstem and hippocampus (18% and 17%, respectively).…”
Section: Effects On Myo-ins Concentrationscontrasting
confidence: 85%
“…As a result, several studies have investigated the effects of inositol administration on brain inositol levels and on changes in psychiatric symptoms in several disorders. Inositol administration has been reported to increase brain inositol concentrations in both rats (Patishi et al, 1996;Kofman et al, 1998;Pettegrew et al, 2001), and humans (Moore et al, 1999); however, acute changes may reverse with chronic administration (Moore et al, 1999;Pettegrew et al, 2001).…”
Section: Effects Of Inositol Administrationmentioning
confidence: 97%
“…Acute and chronic administration of mIns boosts intracellular mIns levels in the brain Kofman et al 1998;Pettegrew et al 2001). In addition, performance of rats on the elevated plus-maze is also improved as mIns reduces anxiety behavior (Einat and Belmaker 2001).…”
Section: Inositol In Ocd Therapymentioning
confidence: 98%
“…Chronic dietary mIns administration of 1.5 g/kg mIns for 22 d increased locomotor activity and inositol concentration in the cerebral cortex and hippocampus of the brains of rats. However, acute intracerebroventricular (ICV) mIns administration of 5 mg did not increase locomotor activity (Kofman et al 1998), although this may be because performance was assessed only 30 min after the acute administration, which may be too early as inositol takes time to be distributed in the brain . Acute IP administration of 5 g/kg of mIns (1 mol/L) increased the mIns level in the rat brain membrane by 17 % whereas chronic IP administration of 1.2 g/kg dosage of mIns (1 mol/L) for 10 d increased the mIns level by 5 % (Pettegrew et al 2001).…”
Section: Inositol In Ocd Therapymentioning
confidence: 99%